Implication of the Multiphase Influx in Well Control and Circulating System - Sonny Irawan; Imros B. Kinif; Muhammad Taufiq Fathaddin; Zulfadli B. Zakaria (Penerbitan Universitas Trisakti, 2020)
A multiphase flow system is commonly faced by oil and gas industries where it constituted of complex design and analysis [1]. Previous studies on the multiphase system have established a number of models including Hagerdon & Brown, Duns & Ros, Orkiszewki and Beggs & Brill [1]. Numerous studies have been carried out on the multiphase system related to production engineering [3]. However, the study on the multiphase system is found limited to be related to well control and drilling management. The multiphase system is interestingly important in well control especially during unwanted circumstances such as kick. Flow behavior and pattern might be different from one phase system where normally only gas kick is considered during design stage of the drilling campaign. Since the multiphase kick might represent different outcome compared to one phase system, an accurate calculation of multiphase kick is desired. Therefore, the purpose of this study is to observe the impact on the multiphase kick with on the pressure drop reading and its connection with a circulating system. The study will cover on Pressure drop calculation using Beggs & Brill correlation by consolidating all the data given from various sources; Identification of flow regime of the multiphase system for the base case with several reference pressure; Sensitivity analysis including the effect of different liquid content and liquid flow rate towards the pressure drop. The expected outcomes from this study are beneficial for well control management where necessary actions to prevent blowout.